Penerapan Metode Ziyadah Jadidah, Muraja’ah Jadidah, dan Muraja’ah Syamilah dalam Penguatan Hafalan Santri di Pondok Pesantren Tahfizh Ibnu Aqil - Nur Sakinah (Journal of Sustainable Education, 2026)
This study aims to analyze the implementation of Ziyadah Jadidah, Muraja’ah Jadidah, and Muraja’ah Syamilah methods in strengthening students’ Qur’anic memorization. The background of this research is based on the importance of balancing new memorization (ziyadah) and systematic revision (muraja’ah) to maintain the quality (itqan) and sustainability of memorization. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving tahfizh teachers and students actively participating in the memorization program. The findings indicate that the Ziyadah Jadidah method plays a crucial role in establishing new memorization foundations through structured submission and strict tajwid supervision. The Muraja’ah Jadidah method strengthens newly memorized verses through intensive and routine repetition under teacher guidance. Meanwhile, Muraja’ah Syamilah functions as a comprehensive revision process to maintain continuity between previously memorized sections, ensuring strong and long-term retention. Supporting factors include a religious learning environment, disciplined program management, and teacher motivation, while inhibiting factors involve student fatigue and limited time management. Overall, these three methods complement each other in forming a systematic and effective memorization reinforcement model.